Clinical lactation studies and the role of pharmacokinetic modeling and simulation in predicting drug exposures in breastfed infants - Anderson, Philip O.; Momper, Jeremiah D. (Journal of pharmacokinetics and pharmacodynamics, 2020)
The relative lack of information on medication use during breastfeeding is an ongoing problem for health professionals and mothers alike. Most nursing mothers are prescribed some form of medication, yet some mothers either discontinue breastfeeding or avoid medications entirely. Although regulatory authorities have proposed a framework for clinical lactation studies, data on drug passage into breastmilk are often lacking. Model-based approaches can potentially be used to estimate the passage of drugs into milk, predict exposures in breastfed infants, and identify drugs that need clinical lactation studies. When a human study is called for, measurement of the drug concentration in milk are often adequate to characterize safety. Data from these studies can be leveraged to further refine pharmacokinetic models with subsequent Monte Carlo simulations to estimate the spread of exposure values. Both clinical lactation studies and model-based approaches have some limitations and pitfalls which are discussed.